Perioperative Management of Antiplatelet Therapy: A Systematic Review and Meta-analysis - Sahrish Shah, MBBS; Meritxell Urtecho, MD; Mohammed Firwana, MBBS; Tarek Nayfeh, MD; Bashar Hasan, MD; Ahmad Nanaa, MD; Samer Saadi, MD; David N. Flynn, MD, MBA; Rami Abd-Rabu, MBBS; Mohamed O. Seisa, MD; Noora S. Rajjoub; Leslie C. Hassett, ML; et al. (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2022)
Objective: To summarize the available evidence about the perioperative management of patients who are receiving long-term antiplatelet therapy and require elective surgery/procedures. Methods: This systematic review supports the development of the American College of Chest Physicians guideline on the perioperative management of antiplatelet therapy. A literature search of MEDLINE, EMBASE, Scopus and Cochrane databases was conducted from each database’s inception to July 16, 2020. Meta-analyses were conducted when possible. Results: In patients receiving long-term antiplatelet therapy and undergoing elective noncardiac surgery, the available evidence did not show a significant difference in major bleeding between a shorter vs longer antiplatelet interruption, with low certainty of evidence (COE). Compared with patients who received placebo perioperatively, aspirin continuation was associated with increased risk of major bleeding (relative risk [RR], 1.31; 95% CI, 1.15-1.50; high COE) and lower risk of major thromboembolism (RR, 0.74; 95% CI, 0.58-0.94; moderate COE). During antiplatelet interruption, bridging with low-molecular-weight heparin was associated with increased risk of major bleeding compared with no bridging (RR, 1.86; 95% CI, 1.24-2.79; very low COE). Continuation of antiplatelets during minor dental and ophthalmologic procedures was not associated with a statistically significant difference in the risk of major bleeding (very low COE). Conclusion: This systematic review summarizes the current evidence about the perioperative management of antiplatelet therapy and highlights the urgent need for further research, particularly with the increasing prevalence of patients taking 1 or more antiplatelet agents.